History Teaching and Identity in the Swedish Multicultural Society - Laila Nielsen (Universidad Autónoma de Madrid, 2015)
Over the past two decades deteriorated equivalence in Swedish schools has led to teachers have faced growing differences regarding students' potential, motivation and school results. However, within Swedish research concerning the role of school in the multicultural society, focus has not been on teachers' experiences, but rather problem-oriented studies on teaching materials, students' opinions and school policies. The objective of the article is to first, on the basis of Anglo-Saxon research and theories, present an analytical tool consisting of four possible strategies for teaching in a multicultural society. The analytical tool will be used to, through the results from semi-structured interviews, compare and discuss seven upper secondary school teachers' experiences from teaching history in the Swedish multicultural society. To justify the relevance of such a discussion in a Swedish context, a brief presentation of Swedish research in the field are given. The teachers interviewed have primarily been chosen from their reputation of being talented, ambitious, and that they believe they have found workable models in their teaching. The comparison and discussion of the seven teachers' experiences showed examples of similarities, but no clear pattern in relation to the four strategies as apparent from the analysis tool. It rather seems as it is foremost the teachers own background, values and educational context that affects what strategies they choose in their teaching. The result can be interpreted as if the space of interpretations regarding the school's intentions is (too) great, which may be an expression of lack of clarity in objectives and guidelines from the current school politics.